The Influence of Trust Perception, Risk Perception, and Promotion on Purchase Intention and Its Impact on Purchase Decision Using Peer-to-Peer Lending Shopee Paylater (A Survey of Generation Z in Greater Bekasi Area) - Imron Rosadi (Jurnal Manajemen dan Bisnis Madani, 2025)
This study examines the influence of trust perception, risk perception, and promotion on purchase intention and their impact on purchasing decisions among Generation Z users of the Shopee Paylater Peer-to-Peer Lending service in the Bekasi area. Using a quantitative approach through a survey of 250 respondents and analysis with PLS-SEM and CVPAT, the results show that trust has a significant positive effect on purchase intention, while risk has a significant negative effect on both purchase intention and purchasing decisions. Promotion does not have a significant effect on purchase intention but has a positive impact on purchasing decisions. These findings highlight the importance of building trust and managing risk to encourage service usage, and indicate that effective promotion plays a greater role in influencing purchasing decisions than in generating initial interest. The practical implication suggests that service providers should focus on marketing strategies that enhance trust and minimize risk to optimize the adoption of Shopee Paylater.